Sezonska dinamika ksilogeneze in floemogeneze pri navadni jelki (Abies alba Mill.) - Gričar, Jožica (Zbornik gozdarstva in lesarstva, 2005)
The dynamics of xylem and phloem growth ring formation in silver fir (Abies alba Mill.) was studied during the growing season 2003. Blocks of tissue, containing phloem, cambium and outer xylem, were taken weekly from two apparently healthy silver fir trees. According to the observations of transverse sections under light microscope, the cambial cell divisional activity began in early May on the phloem and xylem side simultaneously. Priorto this activity, differentiation of one or two layers of the phloem derivatives began to take place. Cambial activity ceased at the end of August.Differentiation of the terminal late wood tracheids adjacent to cambiumwas completed by the end of October and of the phloem cell by the end of September. Cell production on the xylem side of healthy firs was more intense and the variability in widths of the growth rings across the stem circumference was also greater compared to the phloem.
Keywords: Abies alba Mill.; diferenciacija; floem; kambij; ksilem; navadna jelka; sitaste celice; traheide